Maintaining Control of Chronic Obstructive Airway Disease: Adherence to Inhaled Therapy and Risks and Benefits of Switching Devices. (3rd March 2016) - Melani, Andrea S.; Paleari, Davide
Abstract : Asthma and chronic obstructive pulmonary disease (COPD) are major obstructive airway diseases that involve underlying airway inflammation. The most widely used pharmacotherapies for asthma and COPD are inhaled agents that have been shown to be effective and safe in these patients. However, despite the availability of effective pharmacologic treatment and comprehensive treatment guidelines, the prevalence of inadequately controlled asthma and COPD is high. A main reason for this is poor adherence. Adherence is a big problem for all chronic diseases, but in asthma and COPD patients there are some additional difficulties because of poor inhalation technique and inhaler choice. Easier-to-use devices and educational strategies on proper inhaler use from health caregivers can improve inhaler technique. The type of device used and the concordance between patient and physician in the choice of inhaler can also improve adherence and are as important as the drug. Adherence to inhaled therapy is absolutely necessary for optimizing patient control. If disease control is not adequate despite good adherence, switching to a more appropriate inhaled therapy is recommended. By contrast, uninformed switching or switching to less user-friendly inhaler may impact disease control negatively. This critical review of the available literature is aimed to provide a guidance protocol on when a switch may be recommended in individual patients.